Public understanding of sustainable diets and changes towards sustainability: A qualitative study in a UK population sample. (1st February 2023) - Whittall, B.; Warwick, S.M.; Guy, D.J.; Appleton, K.M.
Abstract: Dietary consumption contributes significantly to the environmental impacts of daily life. Changes to consumption are required, but limited work investigates the reasoning underlying relevant dietary choices. This study aimed to explore public understanding of sustainable diets and any willingness or attempts to make changes towards sustainability in a sample of the UK population. A qualitative approach was used. Twenty-one participants (10 males; predominantly young adults; with a range of living circumstances and cooking responsibilities) were interviewed. Interviews were analysed using inductive thematic analysis. Four themes were identified that related to understanding sustainable diets: 'Consistent with the definition by the Food and Agriculture Organisation of the United Nations (FAO)', 'Multiple benefits', 'Unsure' and 'Competing Interests'. Four themes related to making changes: 'Willing, but unsure', 'Small easy changes', 'Enablers' and 'Barriers'. An additional theme 'COVID-19 pandemic' reflected the period when the work was done (February–May 2021). Within these themes, participants were able to define sustainable eating in a manner that was consistent with and incorporated aspects of the definition by the FAO, could identify sustainable actions that they were undertaking or could undertake, and considered these to be beneficial, but there was a lot of uncertainty, and alternative or competing definitions and actions were also given. Participants were also willing to make changes to make their diet more sustainable, and preferences were expressed for small easy changes of high impact, but there was again considerable uncertainty as to what changes to make. Caution due to the small and select sample is required, but suggestions from this work include increasing awareness and knowledge of the environmental impacts of dietary choices, focusing on small easy changes of likely impact and personal benefit, and increasing availability and accessibility to sustainable diets.